Inability To Adapt To Environmental Changes Causes the Declining Performance of Indonesia's Textile Industry - Rima RACHMAWATI; Evi OCTAVIA (International Journal of Environmental, Sustainability, and Social Science, 2023)
The ability of managers in the face of environmental uncertainty is the main key to achieving competitive advantage. The decline in the performance of the Indonesian textile industry is due to the low quality of management accounting. This quantitative research aims to prove that the ability to deal with environmental uncertainties affects the quality of management accounting as well as its impact on the quality of information. The method used in this research is Explanatory verification research to find out what and how far the factors that affect the quality of management accounting information. This study involved textile companies registered with the Indonesian Textile Association, a total population of 85 companies with sampling methods using power analysis at a significance level of 5% with statistical power. Data analysis using Structural Equation Modeling-Partial Least Square includes measurement and structural models. The results of this study prove that the variability of management accounting information systems is built by the variability of environmental uncertainties. While the variability in the quality of management accounting information is formed by the variability of management accounting systems. Following up on the findings of this study, the ability to deal with environmental uncertainties is the main key to optimizing management accounting systems in generating management accounting information.